DEVELOPMENT OF MATHEMATICS LEARNING DEVICES WITH PROBLEM-BASED LEARNING MODEL ON SOCIAL ARITHMETIC MATERIALS FOR CLASS VII SMP/MTs - Widya Junian Jasmara; Sehatta Saragih (Jurnal Prinsip Pendidikan Matematika, 2022)
The implementation of the 2013 curriculum well is determined by developing learning tools. This research produces learning tools in the form of syllabus, lesson plans, and student worksheets with Problem Based Learning models on Social Arithmetic material. This research is a research and development (R&D) using a 4D model. The instrument in this study was a validity instrument in the form of a validation sheet used to validate the syllabus, lesson plans, and LKPD, as well as a practical instrument in the form of a student response questionnaire to determine the practicality of using LKPD. The average score of the syllabus validation results is 3.48 and is categorized as very valid. This shows that the syllabus can be tested. The average score of the RPP validation results is 3.48 and is categorized as very valid. This shows that the RPP can be tested. The average score for LKPD validation is 3.51 and is categorized as very valid. This shows that the LKPD can be tested. The average student response questionnaire results score is 3.47 and is categorized as very practical.